Postmodern Ontology in an Iranian Wdter's Short Story - hosein payandeh (Matn/Pizhūhī-i Adabī, 2010)
There is no single and universal definition of postmodernism to be found in reference books and literary sources, agreed by all theorists and applicable to all types of postmodern stories. Most theorists emphasise that this concept can not be pinned down by a broad and all-inclusive definition. Seeking comprehensive definitions is certainly indicative of a rational approach; yet postmodernisrn, which challenges modem rationality, is in principle against single and universal definitions and instead favours plurality and paradox. Nevertheless, there are links and inter-connections in the various theories of postmodernism which bring certain aspects of postmodern thinkers' ideas close to each other. The blurring of the distinction between imagination and reality in postmodern stories is one of these common ideas, a typical instance of which can be found in the contemporary Iranian author Ali Khodaec's short story Me Up throughout \vintee'. Reading this story according to Brian McHale's theory of postmodernism and then citing similar concepts introduced by Barry. Lewis and David Lodge. will illustrate how close the ideas of these three thinkers are despite their differing terminologies